SYNTHESIS OF HYDRAULIC CIRCUITS OF CONNECTIVE AND ASSEMBLY MODULE - V. V. Pinchuk (Наука и техника)
Compatibility absence of modular component parts of control hydro-blocks leads to reduction of a unification level and limits potential possibilities of their aggregate-modular design. The results pertaining to substantiation and development of hydraulic circuits of the connective and assembly module are given in the paper.